English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-11-01 13:02:23 · 4 answers · asked by badmf777 1 in Science & Mathematics Mathematics

4 answers

-4(-1)^2 - 3(-1)
-4(1) - -3
-4 + 3
= - 1

2006-11-01 13:50:18 · answer #1 · answered by Domanick 2 · 0 0

f(b) = -4b^2 - 3b for f(-1)
f(-1)=-4(-1)^2-3(-1)=-4+3=-1

2006-11-01 21:08:32 · answer #2 · answered by yupchagee 7 · 0 0

substitute -1 for b
-4(-1)^2 -3 (-1) = -4 +3 = -1

2006-11-01 21:07:46 · answer #3 · answered by Steve A 7 · 0 0

b= -1

-4(-1)^2 -3(-1)
-4(1)-3(-1)
-4+3=1

2006-11-01 21:07:41 · answer #4 · answered by deyi32 1 · 0 1

fedest.com, questions and answers